Within‐plant isoprene oxidation confirmed by direct emissions of oxidation products methyl vinyl ketone and methacrolein - Kolby J. Jardine; Russell K. Monson; Leif Abrell; Scott R. Saleska; Almut Arneth; Angela Jardine; Françoise Yoko Ishida; Ana Maria Yanez Serrano; Paulo Artaxo; Thomas Karl; Silvano Fares; Allen Goldstein; et al. (Global Change Biology, 2012)
Isoprene is emitted from many terrestrial plants at high rates, accounting for an estimated 1/3 of annual global volatile organic compound emissions from all anthropogenic and biogenic sources combined. Through rapid photooxidation reactions in the atmosphere, isoprene is converted to a variety of oxidized hydrocarbons, providing higher order reactants for the production of organic nitrates and tropospheric ozone, reducing the availability of oxidants for the breakdown of radiatively active trace gases such as methane, and potentially producing hygroscopic particles that act as effective cloud condensation nuclei. However, the functional basis for plant production of isoprene remains elusive. It has been hypothesized that in the cell isoprene mitigates oxidative damage during the stress‐induced accumulation of reactive oxygen species ( ROS ), but the products of isoprene‐ ROS reactions in plants have not been detected. Using pyruvate‐2‐ 13 C leaf and branch feeding and individual branch and whole mesocosm flux studies, we present evidence that isoprene ( i ) is oxidized to methyl vinyl ketone and methacrolein ( i ox ) in leaves and that i ox /i emission ratios increase with temperature, possibly due to an increase in ROS production under high temperature and light stress. In a primary rainforest in A mazonia, we inferred significant in plant isoprene oxidation (despite the strong masking effect of simultaneous atmospheric oxidation), from its influence on the vertical distribution of i ox uptake fluxes, which were shifted to low isoprene emitting regions of the canopy. These observations suggest that carbon investment in isoprene production is larger than that inferred from emissions alone and that models of tropospheric chemistry and biota–chemistry–climate interactions should incorporate isoprene oxidation within both the biosphere and the atmosphere with potential implications for better understanding both the oxidizing power of the troposphere and forest response to climate change.